Pengembangan E-Modul IPA SMP Berbasis Socio Scientific Issues (SSI) : Systematic Review - Azizah, Hanifah Putri; Ilhami, Aldeva; Hafiza, Nur (Penerbit Widina, Widina Media Utama, 2022)
This research aims to identify junior high school science e-modules based on socio scientific issues (SSI) through literature review. The method used was systematic literature review. The database used to search for literature uses two digital libraries namely Google Scholar, Scopus and Mendeley Web. In order to make the selected literature relevant, the search used the keywords